2010
DOI: 10.1002/cncr.25643
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variables and primary tumor characteristics predictive of the development of melanoma brain metastases and post‐brain metastases survival

Abstract: BACKGROUND: Melanoma patients who develop brain metastases (B-Met) have limited survival and are excluded from most clinical trials. In the current study, the authors attempted to identify primary tumor characteristics and clinical features predictive of B-Met development and post-B-Met survival. METHODS: A prospectively accrued cohort of 900 melanoma patients was studied to identify clinicopathologic features of primary melanoma (eg, thickness, ulceration, mitotic index, and lymphovascular invasion) that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 20 publications
5
86
6
Order By: Relevance
“…Fife et al reported a median age at the time of diagnosis of brain metastasis of 49 and 57 years with a median time from initial diagnosis of melanoma until occurrence of cerebral metastasis of 2.5 and 3.7 years (10). In our study, patients were older when brain metastasis was confirmed (62 years), however, median time to development of cerebral metastasis (2.5 years in our patient group) was comparable with current literature (1.9-2.7 years) (17,18,37,39).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fife et al reported a median age at the time of diagnosis of brain metastasis of 49 and 57 years with a median time from initial diagnosis of melanoma until occurrence of cerebral metastasis of 2.5 and 3.7 years (10). In our study, patients were older when brain metastasis was confirmed (62 years), however, median time to development of cerebral metastasis (2.5 years in our patient group) was comparable with current literature (1.9-2.7 years) (17,18,37,39).…”
Section: Discussionsupporting
confidence: 89%
“…Predictors for OS in patients with malignant melanoma metastatic to the brain have been published previously and include Ldh levels, age, karnofsky index, number of brain metastasis, leptomeningeal spread, presence of extracerebral metastases, melanoma ulceration, histology and neurologic symptoms (10,13,18,25,37,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case also the site's experience was compared with the results published by other authors [1,5,13,14,37,40,46]. Some investigators point to the adverse prognostics significance of the presence of metastases outside the brain, in particular in the lungs, liver, spleen and adrenal glands, and, to a lesser degree, in the bones, lymph nodes and skin [5,6,8,30,31,[33][34][35][40][41][42]. In the site's own material, in a single-variance analysis, it was shown that the co-existence of the metastases in extracranial locations was an adverse prognostic factor, which was, however, not confirmed by the results of the multivariance analysis.…”
Section: Discussionmentioning
confidence: 86%
“…Factors that have been shown to increase the risk for development of CNS metastasis in melanoma patients included male sex, thickness or ulceration of the skin lesion, primary site in the head and neck, mucosal or acral lentiginous tumors and nodular primary lesions 3 . Metastatic tumors often present with more neuropsychiatric symptoms 4 .…”
Section: Dear Editormentioning
confidence: 99%